Review on Core Degradation and Material Migration Research in Light-Water Reactors - Wang, Jun; Wang, Chen; Shi, Kaiyi; Su, Guanghui (Frontiers in Energy Research, 2018)
Core degradation and material migration research is one of the key areas in severe accident research. A review of core degradation and melting materials immigration research in light-water reactor is important to encourage relevant research. In this paper, both relevant experiments and numerical analyses are reviewed. Due to their high cost, there have only been a few experiments on severe accidents performed. They focus on different aspects of core degradation and material migration, including early stage and late stage accidents in both PWRs and BWRs. All the current experimental data should be fully utilized due to the limited data available. On the other hand, the data available from numerical analyses for severe accidents is very extensive. There are already many systemic severe accident codes developed by different organizations. These codes provide severe accident sequences analysis, severe accident prediction, and are also important in security policy formulation. At the end of this paper, relevant work at Xi’an Jiaotong University is introduced.